Physical activity and renal function in the Italian kidney transplant population. Issue 1 (1st January 2020) - Masiero, Lucia; Puoti, Francesca; Bellis, Lia; Lombardini, Letizia; Totti, Valentina; Angelini, Maria Laura; Spazzoli, Alessandra; Nanni Costa, Alessandro; Cardillo, Massimo; Sella, Gianluigi; Mosconi, Giovanni
Abstract: Background: The well-documented benefits of physical activity (PA) are still poorly characterized in long-term kidney transplant outcome. This study analyzed the impact over a 10-year follow-up of PA on graft function in Italian kidney transplant recipients (KTRs). Methods: Since 2002, the Italian Transplant-Information-System collected donor and recipient baseline and transplant-related parameters in KTRs. In 2015, 'penchant for PA' (PA ≥ 30-min, 5 times/week) was added. Stable patients aged ≥18 years at the time of first-transplantation were eligible. KTRs with at least 10-year follow-up were also analyzed. Mixed-effect regression models were used to compare eGFR changes over time in active versus non-active patients. Results: PA information was available for 6, 055 KTRs (active 51.6%, non-active 48.4%). Lower penchant for PA was found in overweight and obese patients (OR = 0.84; OR = 0.48, respectively), in those with longer dialysis vintage (OR = 0.98 every year of dialysis), and older age at transplant. Male subjects showed greater penchant for PA (OR = 1.25). A slower decline of eGFR over time was observed in active KTRs compared to non-active, and this finding was confirmed in the subgroup with at least 10-year follow-up (n = 2, 060). After applying the propensity score matching to reduce confounding factors, mixed-effect regression models corroborated such better long-term trend of graft function preservation in active KTRs. Conclusions: Penchant for PA is more frequent among male and younger KTRs. Moreover, in our group of Italian KTRs, active patients revealed higher eGFR values and preserved kidney function over time, up to 10-years of follow-up.